Dobra wiara w prawie prywatnym międzynarodowym w ramach art. 10 ustawy z dnia 12 listopada 1965 roku: [Good faith in private international law within the framework of article 10 of the law of 12 November 1965] (Studia Prawnicze / The Legal Studies, 2023)
Ustawa z 12 listopada 1965 r. prawo prywatne międzynarodowe rozstrzyga m. in. problem właściwości prawa w sytuacji gdy cudzoziemiec dokonuje czynności prawnej na obszarze danego państwa. Autor artykułu omawia art. 10 ustawy, w którym ustawodawca uzależnia właściwość prawa polskiego, o ile wymaga tego ochrona osób działających w dobrej wierze. Zostają przedstawione dwa odmienne ujęcia. W jednym z nich jest brana pod uwagę okoliczność, czy druga strona wiedziała lub powinna wiedzieć o niezdolności cudzoziemca. W drugim nie. Autor przedstawia historie polskich regulacji w tej materii przytaczając osiągnięcia polskiej przedwojennej doktryny. Ponadto zostają scharakteryzowane także dodatkowe szczegółowe zagadnienia dotyczącej problematyki dobrej wiary w prawie prywatnym międzynarodowym. The Act of 12 November 1965 on Private International Law resolves, inter alia, the problem of the jurisdiction of the law when a foreigner performs a legal act on the territory of a given state. The author of the article discusses Article 10 of the Act, in which the legislator makes the jurisdiction of Polish law contingent on the protection of persons acting in good faith. Two different approaches are presented. One of them takes into account whether the other party knew or should have known of the foreigner's incapacity. The other one does not. The author presents the history of Polish regulations in this matter citing the achievements of Polish pre-war doctrine. In addition, additional specific issues concerning the problem of good faith in private international law are also covered.